NEW TRENDS IN THE DEVELOPMENT OF THE PARTY SYSTEM OF THE CZECH REPUBLIC - Fedorchak, Т. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2018)
The article examines the development of the political process in the Czech Republic following the results of the last regular elections to the Chamber of Deputies of the Parliament, which took place on October 21-22, 2017 under the proportional electoral system. The results of the elections revealed a number of new trends in the development of the parties and the party system of the Czech Republic, which at the same time have many similarities with the ideas of populists and Euro skeptics spread in the CEE region. The analysis of the specific “differentiated electoral barrier” and the Czech electoral legislation is made. The path to victory in the elections of the ANO and the ODS parties, the new in the Czech politics third party-winner – the Pirate party, members of which advocated the maximum protection of individual freedoms and the uncontrolled Internet. It is noted that the traditional and leading parties of the Czech Republic – KDU-CSL, TOP 9, KSCM, CSSD did not achieve the expected success in the Parliament elections. The regularities that emerged during the elections to the Chamber of Deputies were revealed: a steady demand of voters for new leaders, new political forces, the weakening of the positions and authority of political parties that have occupied leading positions for a long period, the change in the current political agenda. Confirmed pan-European trends: the growth of populist sentiment and a significant increase in skepticism towards the leaders of the European Union, which are manifested in many CEE countries.